BRAF Inhibitors for BRAF V600E Mutant Colorectal Cancers: Literature Survey and Case Report - Yasar Subutay Peker; Mehmet Fatih Can; Ismail Hakki Ozerhan; Gokhan Yagci; Nazif Zeybek; Kutan Kavakli; Sedat Gurkok; Alper Gozubuyuk; Onur Genc; Gokhan Erdem; Ahmet Ozet; Mustafa Gerek; et al. (Case Reports in Surgery)
The main method of fighting against colon cancer is targeted treatment. BRAF inhibitors, which are accepted as standard treatment for V600E mutant malign melanomas, are the newest approach for targeted treatment of V600E mutant colorectal cancers. In this case report, we share our experience about the use of BRAF inhibitor vemurafenib on a V600E mutant metastatic right colon adenocarcinoma patient. A 59-year-old male with only lung multiple metastatic V600E mutant right colon cancer presented to our clinic. The patient was evaluated and FOLFOX + bevacizumab treatment was initiated, which was then continued with vemurafenib. A remarkable response was achieved with vemurafenib treatment in which the drug resistance occurred approximately in the sixth month. Even though the patient benefited majorly from vemurafenib, he died on the 20th month of the diagnosis. The expected overall survival for metastatic V600E mutant colon adenocarcinoma patients is 4.7 months. BRAF inhibitors provide new treatment alternatives for V600E mutant colorectal cancers, with prolonged overall survival. BRAF inhibitors in combination with MEK inhibitors are reported as feasible treatment to overcome BRAF inhibitor drug resistance on which phase studies are still in progress. To conclude, BRAF inhibitors alone or in combination with other drugs provide a chance for curing BRAF V600E mutant colorectal cancer patients.